Performance, metabolic variables and enteric methane production of Santa Inês hair lambs fed Orbignya phalerata and Combretum leprosum. Issue 3 (30th August 2016) - Abdalla Filho, A. L.; Dineshkumar, D.; Barreal, M.; McManus, C.; Vasconcelos, V. R.; Abdalla, A. L.; Louvandini, H.
Summary: In this study, the possibility of using Babassu ( Orbignya phalerata ) and Mofumbo ( Combretum leprosum ) leaves for lambs feed was verified. Performance, biochemical and haematological parameters, microbial protein synthesis, nutrient apparent digestibility and enteric production of methane (CH4 ) were evaluated. The experimental treatments included diets with forage‐to‐concentrate ratios of 50:50, with the leaves of the experimental plants replacing 33% of the Cynodon dactylon (Tifton‐85) hay with three treatments: control (no hay replacement) and substitution with Babassu or Mofumbo. For the performance study, 24 Santa Inês lambs were used, in a randomized experimental design with eight repetitions (5 male and 3 female) for each treatment and 48 days of experimental trial. After this period, for nine days, six animals from each treatment were allocated in metabolic cages to determine the apparent nutrient digestibility, microbial protein synthesis and nitrogen balance. Simultaneously, enteric CH4 was measured in vivo . The control group showed higher (p < 0.05) apparent digestibility of acid detergent fibre. Enteric CH4 production of lambs fed Mofumbo leaves did not differ from that of the control group, but was lower (p < 0.05) than in those fed with Babassu. The inclusion of Babassu and Mofumbo leaves showed no negative effects on animal health and did not compromise performance. Mofumbo also presented CH4 mitigating potential, indicating that those plants can be used as ingredients in the composition of lamb diets with the advantage of reducing methane production.